Clinical Profile And Risk Factors Of Stroke: A Comparative Analytical Study Between Young And Old Onset - Reza Stevano; Jacqueline Tasha Margono; Anyeliria Sutanto (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2023)
Background: With ever-increasing incidence, young-onset stroke is responsible for significant psychosocial and economic burden, primarily due to post-stroke disability in the productive population. Objective: The aim of our study is to assess the profile and risk factors in young-onset stroke compared to those in older patients. Methods: This was a retrospective cross-sectional study. We included all patients with acute stroke, or transient ischemic attack (TIA) treated at Siloam Lippo Village Hospital between October 2021 and February 2022. An independent t-test was conducted for continuous variables with normal distribution and a Mann-Whitney U test for ordinal or continuous variables with non-normal distribution. Pearson's chi-square test was performed for categorical variables. Results: 153 patients with acute stroke and TIA were included. On univariate analysis comparing young and old-onset strokes, significant differences were found in diagnosis (p=0.039), Bamford classification (p=0.022), NIHSS (p=0.014), history of smoking (p=0.012), previous stroke (p=0.045), history of coronary artery disease (p=0.026), and routine antiplatelet use (p=0.018). Conclusion: We found a predominance of hemorrhagic stroke and TIA in the young-onset group, with more common involvement of the anterior circulation. Older onset was associated with a higher NIHSS score. Modifiable risk factors are more common in young-onset stroke, while non-modifiable risk factors are more common in the older population. However, hypertension remains an equally important risk factor in both groups. Our study provides an overview of the profile and risk factors for young-onset stroke. The information obtained can be useful as educational material for the community to prevent young-onset stroke.